Pectin preparation from calamansi seeds and watermelon rind - Magwili, Teresita H.
Dried powdered pectin from the seeds of calamansi and the rind of watermelon was prepared and analyzed in this study. Objective evaluation of pectin from calamansi seeds was satisfactorily done. The powdered pectin was highly methoxylated. Methoxyl content of the pectin for trials 1, 2 and 3 were 15.%, 10.5% and 12.9%, respectively. The jelly grade was found to be 13.6 based on the prepared test jellies. The total pectin content obtained was 4.2% on a wet sample basis. The pectin prepared from the watermelon rind has a lower degree of methoxylation than that of the calamansi seeds. The following values were obtained for the first, second and third trials: 3%, 4.8% and 6.3%. Attempts to prepare test jellies were not successful. Only viscous solutions resulted from the preparation. The total pectin content of the wet sample based on three trials was .9%. The study undertaken has evaluated the feasibility of recovering pectin from calamansi and watermelon.